Ecologias: sobre processos educativos livres e libertários em movimentos sociais pós-modernos - Franques, Bruno Marcondes (2014)
Applying complexity and transdisciplinarity that the ecology of knowledge - among other systemic perspective -, this dissertation focuses on education in their studies and analysis of contemporary social movements - the transition period in which we see the values of the paradigm of modernity being questioned by these same movements already providing new perspectives which replace that - with the assumption exercising their educational role and identifying the libertarian character which pierces the new forms of organization and values set in motion by such movement, we recognizing the changing ecological perspectives to see them incorporated into the new rising paradigm, this paradigm identified as a libertarian post-modernity